Deoxyribonucleic acid synthesis in a temperature-sensitive Escherichia coli dnaH mutant, strain HF4704S. - Derstine, P L (1976)
The dnaH mutant strain HF4704S, isolated by Sakai et al. (1974), was examined for its effect on phiX174 deoxyribonucleic acid (DNA) synthesis. It was found to carry two mutations affecting DNA synthesis. One mutation had no affect on phiX174 DNA synthesis, but did affect the ability of the mutant cells to form colonies on agar medium at 41 degrees C, and caused host DNA synthesis to cease after 1 h at 41 degrees C. The mutant marker cotransduced with ilvD at a frequency of about 9%. It seems likely that this mutation is in the dnaA gene. The second mutation affected the ability of the mutant cells to form colonies on agar medium supplemented with only 2 mug of thymine per ml, and affected both host and phiX174 DNA synthesis in medium supplemented with only 2 mug of thymine per ml. Both effects could be overcone by adding excess exogenous thymine. We were not able to unambiguously determine the map position of this mutant locus. Our data show that the DNA synthesis phenotype of the mutant strain HE4704S is governed by both these mutations, neither of which directly affects the replication of phiX174 DNA.